Pelonaia quadrivena n. sp.a case of bipolarity in Ascidiacea - Monniot, Françoise (Zootaxa, 2011)
A new ascidian species of the genus Pelonaia (Ascidiacea, Styelidae) is decribed from the coastal shore of Terre Adélie, Antarctic. The genus was referenced by a single species widely distributed in the arctic seas. Comparative anatomical descriptions are given for the species of both hemispheres. The validity of the genus is confirmed.